2020
DOI: 10.1136/tobaccocontrol-2019-055553
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to JUUL use: cue reactivity effects in young adult current and former smokers

Abstract: BackgroundExposure to the use of first, second and third generations of electronic cigarettes (e-cigarettes) elicits the desire to vape and smoke among observers, as well as facilitates smoking behaviour. Given the rapid rise in the popularity of the pod mod JUUL, we examined whether observing the use of this device would elicit similar responses in smokers. Exploratory analyses were also conducted to determine whether JUUL can act as a smoking cue for former smokers.MethodsThe sample consisted of 82 young adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The addictive ‘potential’ of JUUL, whose nicotine content is claimed to be equivalent to a pack of 20 cigarettes ( Bowen and Xing, 2014 , The Truth Initiative, 2021 , JUUL Labs, Inc, 2021a ), together with the immense popularity of JUUL among teens and young adults ( Hammond et al, 2020 , Goniewicz et al, 2019 , Hrywna et al, 2020 ) has raised concern that a new generation of tobacco product users may be en route to nicotine dependence and addition ( Lee et al, 2020 , Creswell, 2019 ). There is also concern that JUUL use in youth may lead to gateway effects, such as initiation of smoking or cannabis use ( Jenssen and Wilson, 2019 , Case et al, 2020 , Vena et al, 2020 ). Furthermore, JUUL vapor inhaled by users, is shown to contain many of the same toxicants and carcinogens as those found in tobacco smoke ( Reilly et al, 2019 , Talih et al, 2019 , Talih et al, 2020 , Mallock et al, 2020 ).…”
Section: An Introduction To Juul and Youth Vaping Epidemicmentioning
confidence: 99%
“…The addictive ‘potential’ of JUUL, whose nicotine content is claimed to be equivalent to a pack of 20 cigarettes ( Bowen and Xing, 2014 , The Truth Initiative, 2021 , JUUL Labs, Inc, 2021a ), together with the immense popularity of JUUL among teens and young adults ( Hammond et al, 2020 , Goniewicz et al, 2019 , Hrywna et al, 2020 ) has raised concern that a new generation of tobacco product users may be en route to nicotine dependence and addition ( Lee et al, 2020 , Creswell, 2019 ). There is also concern that JUUL use in youth may lead to gateway effects, such as initiation of smoking or cannabis use ( Jenssen and Wilson, 2019 , Case et al, 2020 , Vena et al, 2020 ). Furthermore, JUUL vapor inhaled by users, is shown to contain many of the same toxicants and carcinogens as those found in tobacco smoke ( Reilly et al, 2019 , Talih et al, 2019 , Talih et al, 2020 , Mallock et al, 2020 ).…”
Section: An Introduction To Juul and Youth Vaping Epidemicmentioning
confidence: 99%
“… 67 Of the remaining three papers that did not include smokers, one included participants who had never smoked and did not currently smoke, 68 one assessed only exclusive ENDS users, 69 and one included both current and former smokers but analysed the groups separately. 70 All papers used visual cues.…”
Section: Resultsmentioning
confidence: 99%
“…79 , 82 In regards to nicotine content, only 10 studies reported the ENDS nicotine levels used in their experiments. 64 , 69 - 72 , 74 , 77 , 79 - 81 E-liquids nicotine content ranged from 0 to 59 mg/ml (salt). Further information about ENDS types and nicotine levels used in the reviewed studies, including related outcomes, is presented in the sub-sections below and in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations